1989
DOI: 10.1093/ajcn/50.2.329
|View full text |Cite
|
Sign up to set email alerts
|

Serum vitamin A and retinol-binding protein in patients with insulin-dependent diabetes mellitus

Abstract: Serum concentrations of vitamins A and E and retinol-binding protein (RBP) were measured in 25 late adolescent and young adult patients with insulin-dependent diabetes mellitus. Their serum vitamin A levels were significantly lower than those of nondiabetic control subjects of comparable age. The serum concentrations of RBP were also significantly lower in the diabetic patients. The serum levels of vitamin A in the diabetic patients as well as in the control subjects showed a significant linear regression with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
61
3
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 87 publications
(77 citation statements)
references
References 18 publications
12
61
3
1
Order By: Relevance
“…This is further supported by the observation that retinyl ester hydrolase activity in liver was found to be decreased in T1D rat models, but not in intestine, in agreement with increased hepatic accumulation without changes in the intestinal absorption of retinol (51). It is also possible that the decrease in plasma retinol and/or RBP4 could be a result of increased renal filtration due to low plasma TTR concentrations during T1D (40,41). It has been reported that plasma TTR concentrations were depressed in newly diagnosed T1D human subjects as well as in T1D rat models (29,32,41).…”
Section: Plasma Rbp4 Ttr and Retinol Levels In Type 1 Diabetessupporting
confidence: 56%
See 3 more Smart Citations
“…This is further supported by the observation that retinyl ester hydrolase activity in liver was found to be decreased in T1D rat models, but not in intestine, in agreement with increased hepatic accumulation without changes in the intestinal absorption of retinol (51). It is also possible that the decrease in plasma retinol and/or RBP4 could be a result of increased renal filtration due to low plasma TTR concentrations during T1D (40,41). It has been reported that plasma TTR concentrations were depressed in newly diagnosed T1D human subjects as well as in T1D rat models (29,32,41).…”
Section: Plasma Rbp4 Ttr and Retinol Levels In Type 1 Diabetessupporting
confidence: 56%
“…Furthermore, the low retinol phenotype also appears to be heritable among T1D subjects, suggesting an inherent metabolic link between T1D and vitamin A transport. Basu et al (40,41) also reported declined plasma vitamin A levels in T1D adults. Interestingly, plasma levels of vitamin A in diabetic patients as well as in the control subjects showed a significant linear regression with plasma concentrations of RBP4, suggesting incomplete mobilization from liver stores or increased renal clearance of RBP4 (40,41).…”
Section: Plasma Rbp4 Ttr and Retinol Levels In Type 1 Diabetesmentioning
confidence: 92%
See 2 more Smart Citations
“…Several studies have reported that serum levels of both carotene and vitamin A are within normal range in diabetes mellitus (Murrill et al, 1941;Kimble et al, 1946;Ramachandran, 1973). Recently, an increase in plasma retinyl esters has been reported in Type 2 diabetes (Wako et al, 1986) and a decrease in serum concentration of vitamin A and RBP in Type 1 diabetes (Basu et al, 1989). Other investigators found that retinol concentrations were signi®cantly decreased in Type 1 (Krempf et al, 1991) and increased in Type 2 diabetes mellitus as compared to control subjects (Krempf et al, 1991;Havivi et al, 1991;Sasaki et al, 1995).…”
Section: Introductionmentioning
confidence: 97%